Optimization of Deployable Antennas: Material, Structure and Drive Mode - Xiaohan Li; Sigen A (Innovation in Science and Technology, 2024)
This research investigates the optimisation of deployable antennas by focusing on material selection, structural design, and drive mode. Deployable antennas are crucial for applications such as satellite communication and remote sensing. The study aims to enhance their efficiency and reliability through a comprehensive optimisation approach. A systematic review identifies suitable materials based on mechanical, electrical, and environmental properties. The structural design analysis explores various deployment mechanisms, such as foldable, inflatable, and tensegrity structures. Additionally, the drive mode optimisation examines actuation methods, including motor-driven, shape memory alloy, and piezoelectric systems, assessing their precision, energy consumption, and adaptability. The findings contribute to the development of more efficient, reliable, and versatile deployable antennas, improving the capabilities of communication systems.